2014
DOI: 10.1073/pnas.1402336111
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbes drive intestinal inflammation by IL-17–producing CD4 + T cells through ICOSL and OX40L costimulation in the absence of B7-1 and B7-2

Abstract: The costimulatory B7-1 (CD80)/B7-2 (CD86) molecules, along with T-cell receptor stimulation, together facilitate T-cell activation. This explains why in vivo B7 costimulation neutralization efficiently silences a variety of human autoimmune disorders. Paradoxically, however, B7 blockade also potently moderates accumulation of immune-suppressive regulatory T cells (Tregs) essential for protection against multiorgan systemic autoimmunity. Here we show that B7 deprivation in mice overrides the necessity for Tregs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Furthermore, our data have determined that Th17 cells differentiated in absence of CD28 costimulation are responsive to restimulation rather than becoming anergic. ICOS and OX40L have been proposed as alternate costimulatory molecules to support Th17 differentiation (Paulos et al, 2010; Xin et al, 2014). We did not compare these in our study, as we found that stimulation with anti-CD3 and cytokines alone gave consistent Th17 responses, but it is possible there would be a further additive effect if these costimulatory molecules were present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our data have determined that Th17 cells differentiated in absence of CD28 costimulation are responsive to restimulation rather than becoming anergic. ICOS and OX40L have been proposed as alternate costimulatory molecules to support Th17 differentiation (Paulos et al, 2010; Xin et al, 2014). We did not compare these in our study, as we found that stimulation with anti-CD3 and cytokines alone gave consistent Th17 responses, but it is possible there would be a further additive effect if these costimulatory molecules were present.…”
Section: Discussionmentioning
confidence: 99%
“…In our own hands, we have not found a consistent effect of CD28 costimulation on mouse Th17 cells. However, B7-deficient mice develop spontaneous colitis mediated by commensal-specific Th17 cells along with decreased T-reg cells (Xin et al, 2014), suggesting that, in mucosal sites in vivo , similar mechanisms of CD28-mediated Th17 regulation may occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, GI tract inflammation was shown to promote C. albicans colonization in chemically induced colitis in mice, which augments inflammatory responses via the PRR galectin-3 (116). C. albicans colonization also primed expansion of Th17 cells with commensal specificity, driving intes-tinal inflammation (117). Likewise, C. albicans colonization of the GI tract in germfree animals induced gastritis, demonstrating the inflammatory potential of this "benign" microbiota member (13).…”
Section: Non-cd4mentioning
confidence: 94%
“…The following day, the culture was washed and suspended in sterile saline. Antibiotic treated mice were administered an oral lavage of 10 6 fungal CFUs (in 30 µL phosphate-buffered saline) via P200 micropipette (Xin et al, 2014). …”
Section: Star Methodsmentioning
confidence: 99%